คำตอบ

2014-02-19T21:07:25+07:00
3x - 5y  =  -4  ------------------------- (1)
6x + 7y =  -3  ------------------------- (2)

นำ (1) คูณด้วย 2 จะได้ 6x - 10y = -8 ------------------------- (3)

นำ (2) - (3) จะได้ 6x + 7y - (6x - 10y) = -3 - (-8)
                        6x + 7y - 6x + 10y  = -3 + 8
                                         17y       = 5
                                             y      =  \frac{5}{17}

แทนค่า y ใน (1) จะำได้  3x - 5( \frac{5}{17} )  =  -4
                                         
                                  3x -  \frac{25}{17} = -4
                                                   
                                                    3x                   =  -4 +  \frac{25}{17}
                                                   
                                                    3x                   =   \frac{93}{17}
                                                     
                                                      x                   =  \frac{93}{17}  × \frac{1}{3}
                                                     
                                                       x                  =  \frac{31}{17}